Pelaksanaan Ekstrakurikuler Paduan Suara Di SMP Adabiah Padang - Novia Mapriscka Utami; Ardipal Ardipal (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
This research aims to describe the implementation of choir extracurricular activities at Adabiah Middle School in Padang. This type of research is qualitative research with a descriptive approach. The object of the research is the implementation of choir extracurricular activities at Adabiah Middle School in Padang. The research instrument is the researcher himself and is assisted by supporting instruments. Data analysis techniques by collecting data, clarifying data and concluding data. This research shows that the results of the extracurricular choir implementation at Adabiah Padang Middle School went quite well. This program is designed through structured stages, starting from providing information to students, registration, designing and determining the schedule, to selecting and presenting songs as well as grouping two types of high and low voices in the soprano and alto ranges. Each practice session includes teaching choral concepts, breathing techniques, voice production, and practice of the song "Satu Nusa Satu Bangsa." The evaluation showed that there were challenges in the distribution of sounds and vocal techniques, but overall this activity was successful in improving students' vocal skills, self-confidence and appreciation for the art of vocal music. This success is supported by effective collaboration between trainers and arts and culture teachers, ensuring smooth implementation and achieving satisfactory results based on harmonization, precision of tone and soulfulness of the song. The final results show that the choir extracurricular program at Adabiah Middle School in Padang has succeeded in achieving the expected goals.